If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -7 = 4m + 5 Reorder the terms: -7 + 8m = 4m + 5 Reorder the terms: -7 + 8m = 5 + 4m Solving -7 + 8m = 5 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. -7 + 8m + -4m = 5 + 4m + -4m Combine like terms: 8m + -4m = 4m -7 + 4m = 5 + 4m + -4m Combine like terms: 4m + -4m = 0 -7 + 4m = 5 + 0 -7 + 4m = 5 Add '7' to each side of the equation. -7 + 7 + 4m = 5 + 7 Combine like terms: -7 + 7 = 0 0 + 4m = 5 + 7 4m = 5 + 7 Combine like terms: 5 + 7 = 12 4m = 12 Divide each side by '4'. m = 3 Simplifying m = 3
| -2(c-1)=-22 | | x^3-3x^2+3=27 | | 6(y+1)=6 | | X^2+6-10=0 | | 18-n=n | | x^4-7x^2+9=27 | | 3(a-4)=33 | | 22=4+8c-2e | | 2x-6=54-4x | | 24(5x+11)=88(18) | | y-q=m(x-p) | | 5x^3y+10x^2y-40xy=0 | | 2x+3=-3x-4 | | 15x-10y=32 | | 24=5r+r*r | | 2-n=7-2n | | 11a-3a+9=-7 | | 8-2n=26 | | x+13=49 | | x^2-7x+42=0 | | 9x^3y+81x^2y-90xy=0 | | 7p+3=-11 | | x+3x+x+3x=64 | | 4-2p=6 | | 8x-30+6x-21=10x-27+2x+9 | | P(x)=x^4+7x^3-50x^2+30x-24 | | -1(1+7x)-6(-7-1x)=36 | | x^4+3x^3+2x^2+30x=0 | | g+g+9=29 | | 3x^2-13x-56=0 | | 45xy^4-30xy^2z+5xz^2=0 | | 14-9=12+18 |